MORAL CRISIS IN A CONSUMER SOCIETY: A MORAL PHILOSOPHY PERSPECTIVE ON A MATERIALIST LIFESTYLE - Putri, Melinda Dita (Al-Imtaz: Jurnal Keilmuan Ushuluddin, 2025)
A lifestyle oriented towards excessive consumption and material possession has caused a shift in moral values in society. Values that once upheld simplicity, solidarity, and social responsibility have now been replaced by the urge to satisfy consumer desires and self-image through material possession. This phenomenon marks the occurrence of an ethical crisis that is increasingly rooted in modern culture. This article examines how moral philosophy, especially deontological ethics and utilitarianism, views the impact of a materialistic lifestyle on this moral crisis. Through critical analysis, it is found that excessive materialism tends to ignore moral values such as honesty, empathy, and social responsibility. As a result, society experiences moral degradation characterized by individualism, hedonism, and social indifference. To overcome this crisis, efforts are needed to revitalize moral values through ethical education, philosophical reflection, and social policies that support a balance between material and spiritual needs.